EDUKASI HUKUM WARIS ISLAM SEBAGAI UPAYA PENCEGAHAN SENGKETA KELUARGA DI MASYARAKAT - Habibah Zulaiha; Mohammad Solekhan; Taupiq; Siti Mahmudah (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2026)
Inheritance disputes within families often arise from limited public understanding of Islamic inheritance law, weak communication among heirs, and the persistence of local inheritance practices that are not always aligned with the principles of justice in Islamic law. This community service program aims to enhance public literacy on Islamic inheritance law as a preventive effort to reduce family disputes in society. The program was implemented through participatory legal education, legal counseling, case discussions, and simple simulations of inheritance distribution based on the principles of farā’iḍ. The participants consisted of community members, religious leaders, local figures, and families potentially facing inheritance-related issues. The educational materials covered the basic concepts of Islamic inheritance law, the pillars and requirements of inheritance, causes and impediments to inheritance, classifications of heirs, principles of justice in inheritance distribution, and the importance of family deliberation in resolving inheritance matters. The results indicate that education on Islamic inheritance law improved participants’ understanding of the rights and obligations of heirs, reduced misconceptions regarding inheritance distribution, and strengthened public awareness of resolving inheritance issues fairly, peacefully, and in accordance with Islamic legal principles. This program affirms that Islamic inheritance law literacy plays an important preventive role in minimizing family conflict, strengthening social harmony, and fostering a more orderly legal culture within society. Therefore, education on Islamic inheritance law should be conducted continuously through collaboration among academics, religious leaders, village authorities, and community-based religious institutions.